The impact of risk regulation on price dynamics - Danı́elsson, Jón; Shin, Hyun Song; Zigrand, Jean-Pierre (Journal of Banking & Finance, 2004)
Most financial risk regulations assume that asset returns are exogenous, where risk is estimated from historical data. This assumption fails to take into account the feedback effect of trading decisions on prices. We investigate the consequences of risk constrained trading by means of simulations of a general equilibrium model with a value-at-risk constraint and compare the results to the case when risk constraints are not present. Prices are lower on average in the presence of risk regulation, while volatility is higher. Risk regulation may have the perverse effect of exacerbating price fluctuations.